ECHOGRAPHIC PATTERN OF THE ABDOMINAL ORGANS OF THE DOMESTIC RABBIT (ORYCTOLAGUS CUNICULUS) - Cahua U., Jacqueline (2014)
The present study aimed to determine the quantitative echographic pattern of abdominal organs of the domestic rabbit. Ultrasound examination was performed in 16 New Zealand mature rabbits (11 females and 5 males). Descriptive measurements were obtained for liver (diaphragm hilum, dorsal ventral and transverse diameter), gallbladder (length and thickness), gastric wall, urinary bladder (wall, length and thickness), spleen (length, thickness and transverse diameter), kidneys (length, thickness and cortex), prostate (length, thickness and diameter) and uterine body.